Og meets Mog! - Dyckman, Ame (Dyckman, Ame. Monster Og., 2024)
"Og is a thoughtful monster who stumbles upon a curious creature trapped in a block of ice! Will Og come up with the perfect plan to break the ice, and possibly make a new friend?"--